2019
DOI: 10.1016/j.nicl.2019.101668
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific structural abnormalities in major depressive disorder revealed by fixel-based analysis

Abstract: BackgroundMajor depressive disorder (MDD) is a chronic disease with a large global impact. There are currently no clinically useful predictors of treatment outcome, and the development of biomarkers to inform clinical treatment decisions is highly desirable.MethodsIn this exploratory study we performed fixel-based analysis of diffusion MRI data from the International Study to Predict Optimized Treatment in Depression with the aim of identifying novel biomarkers at baseline that may relate to diagnosis and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Across both sexes, lower fiber cross-section, an approximation of the fiber bundle area perpendicular to fiber length, in the tapetum predicted decreased likelihood for remission after antidepressant treatment [Lyon et al, 2019]. As the tapetum is the major connector between the left and right hippocampus, these findings align with existing studies by our group and others implicating the hippocampus as a common site for brain disruption in MDD.…”
Section: Major Depressive Disordersupporting
confidence: 87%
“…Across both sexes, lower fiber cross-section, an approximation of the fiber bundle area perpendicular to fiber length, in the tapetum predicted decreased likelihood for remission after antidepressant treatment [Lyon et al, 2019]. As the tapetum is the major connector between the left and right hippocampus, these findings align with existing studies by our group and others implicating the hippocampus as a common site for brain disruption in MDD.…”
Section: Major Depressive Disordersupporting
confidence: 87%
“…Higher prevalence of depression in women was associated with hormonal changes (Marrocco and McEwen, 2016) and sex chromosome aneuploidies (Green et al, 2019). Neuroimaging studies of structural changes of the genu of the corpus callosum may implicate different risk of depression between genders (Lyon et al, 2019). Moreover, gut microbiota-immune-brain axis function may also contribute to gender differences in depression (Audet, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…FBA facilitates fiber tract-specific comparisons, in contrast to analyses of voxel-averaged metrics. This method has been used to detect white matter alterations in several diseases, including Alzheimer’s disease ( Mito et al, 2018 ), Major Depression Disorder ( Lyon et al, 2019 ), and Multiple Sclerosis ( Gajamange et al, 2018 ), and has been shown to demonstrate good sensitivity and reliability.…”
Section: Introductionmentioning
confidence: 99%